Climate Analysis to Predict Potential Spread and Seasonality for Global (COVID-19) in Iraqi Kurdistan Region - M. Amin, Hemin Nasraldin; M. Amin, Hero Nasraldin (Kurdistan Journal of Applied Research, 2020)
The present study is about the relationship of the climate to the possibility of turning (COVID-19) into a seasonal epidemic in Iraqi Kurdistan region. The study area is located in the northern Iraq, within subtropical zone in northern hemisphere, it lies between two latitudes (32° 38’ – 37° 22’) N and longitudes (41° 18’ – 46° 21’) E. It surrounded by Turkey from north, the Islamic Republic of Iran from east, Syria from northwest and with other parts of Iraq from south and west. To achieve the aim of this study, these topics were analyzed (climatic analysis to spatial variation of (COVID-19) outbreak through the world, climatic characteristics of the study area, and seasonal and spatial danger degree analysis to (COVID-19) in the study area). The evidences indicated that cold and dry conditions may facilitate the spread of the virus. According to the study area the lower the temperature is the greater relative humidity will be and vice versa. Therefore, the study assumed that seasonal differences of temperature and humidity in different regions of the study area might contribute to the balanced risk of infection with the virus.